Advanced Strategies of CAR-T Cell Therapy in Solid Tumors and Hematological Malignancies - Liu, Yangjie; Peng, Cao; Ahad, Faiza; Ali Zaidi, Syed A.; Muluh, Tobias Achu; Fu, Qiuxia (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Chimeric antigen receptor T-cells, known as CAR-T cells, represent a promising breakthrough in the realm of adoptive cell therapy. These T-cells are genetically engineered to carry chimeric antigen receptors that specifically target tumors. They have achieved notable success in the treatment of blood-related cancers, breathing new life into this field of medical research. However, numerous obstacles limit chimeric antigen receptors T-cell therapy's efficacy, such as it cannot survive in the body long. It is prone to fatigue and exhaustion, leading to difficult tumor elimination and repeated recurrence, affecting solid tumors and hematological malignancies. The challenges posed by solid tumors, especially in the context of the complex solid-tumor microenvironment, require specific strategies. This review outlines recent advancements in improving chimeric antigen receptors T-cell therapy by focusing on the chimeric antigen receptors protein, modifying T-cells, and optimizing the interaction between T-cells and other components within the tumor microenvironment. This article aims to provide an extensive summary of the latest discoveries regarding CAR-T cell therapy, encompassing its application across various types of human cancers. Moreover, it will delve into the obstacles that have emerged in recent times, offering insights into the challenges faced by this innovative approach. Finally, it highlights novel therapeutic options in treating hematological and solid malignancies with chimeric antigen receptors T-cell therapies.
Keywords: Chimeric antigen receptors